Determinants of Word of Mouth in Universities: A Study of Private Universities in Banten, Indonesia - Alfatiyah, Rini; Limakrisna, Nandan; Muharam, Hari (International Journal of Management and Digital Business, 2023)
In facing this globalization Era, the wheel of educational competition must be designed in such a way that the educational process can go hand in hand with the development of advanced technology. many potential residents of Banten who will continue their education to college. This study aims to determine and analyze the impact of Brand Image, service quality, and Customer Relationship Management on word of mouth in private universities in Banten. In this study the sample size is determined in the form of statistical tests that will be used is a model of structural Equation Modeling (SEM). the sample in this study was as many as 354 student respondents from 5 private universities in Banten province, while the population in this study was 32,637 students. The sampling method used in this study is to use probability sampling. Questionnaires collected data. The Data were analyzed by structural equation modeling (SEM) and its tools using Lisrel 8.80. The results revealed that brand image has a positive and significant effect on word of mouth, Service Quality has a positive and significant impact on word of mouth, and Customer Relationship Management has a positive and significant effect on word of mouth.